Quality of Food and the Birth of Offers of a Certain Sex (Experimental Study) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article describes hypotheses for determining the sex of a child; it must be pointed out that not a single hypothesis has yet found scientific confirmation. In some experimental animals, a   relationship was discovered between the acidity of the nutrient medium in which gametes float and the sex of the unborn child. In this regard, the purpose of this work was to study the influence of the qualitative composition of the diet on the birth of sex. This paper presentspreliminary research results that require more in-depth study and at a higher methodological level. This issue, which concerns everyone, is in the early stages of resolution.